Influence of carbon-to-phosphorus ratios on phosphorus fractions transformation and bacterial community succession in phosphorus-enriched composting. (October 2022) - Chen, Wenjie; Zhan, Yabin; Zhang, Xinjun; Shi, Xiong; Wang, Zhigang; Xu, Shaoqi; Chang, Yuan; Ding, Guochun; Li, Ji; Wei, Yuquan
Graphical abstract: Highlights: C/P at 50 could promote AP accumulation in P-enriched composting. High C/P was beneficial for increasing MBP in P-enriched composting. Initial C/P affected the topology structure of bacterial co-occurrence network. Mesorhizobium and Pseudomonas were identified as core species for AP transformation. C/P indirectly affected bacterial P cycle genes to regulate AP and MBP accumulation. Abstract: This study aims to assess the effect of different carbon-to-phosphorus (C:P) ratios on phosphorus (P) fractions transformation, bacterial community succession and microbial P-solubilizing function in kitchen waste composting with rock phosphate (RP) amendment and phosphate-solubilizing bacteria (PSB) inoculation. Results indicated that initial C:P ratio at 50 enhanced organic carbon degradation, available P (AP) accumulation, the amount of PSB and pqqC gene abundance in composting but higher C:P ratio increased microbial biomass phosphorus (MBP) content. Redundancy analysis showed C:P ratios, PSB amount and pqqC gene abundance greatly affected bacterial community diversity and composition. Network analysis indicated that lower C:P ratio enhanced the interaction frequency in core bacterial network for AP transformation. Variance partitioning analysis abiotic factors contributed more to MBP and AP conversion. The study revealed that C:P ratio could directly drive PSB to regulate P fractions and the accumulation of MBP or AP in P-enriched composting.